Prevalence of abuse among the elderly population of Syangja, Nepal - Shiva Raj Acharya; B. K. Suman; Sandip Pahari; Yong Chul Shin; Deog Hwan Moon (BMC, 2021)
Abstract Background Elder abuse is recognized as a serious public health concern and top priority aging issues. World Health Organization reported that around 1 out of 6 old people in the world experienced some form of abuse. This study was carried out to find out the prevalence of different forms of abuse among elderly Nepalese people. Methods The cross-sectional, quantitative analytical study was carried out among 373 elders of the Syangja district of Nepal. The study population was selected through simple, proportionate, and systematic sampling methods. Data was collected through face-to-face interviews using a structured questionnaire. Results The majority of participants were female (54.5%). The prevalence of elderly abuse was found to be 54.5%. The most common form of abuse among the elderly population was neglect (23.1%), psychological abuse (20.6%), physical abuse (6.5%), financial abuse (2.4%), and sexual abuse (1.9%). Elderly females were significantly more likely to experience physical and psychological abuse. Conclusion More than half of the elderly experienced at least one form of abuse. Neglect was found to be the most common form of abuse. The abuse was prevalent among elderly who were ill and with the habit of tobacco and alcohol consumption.